Immigrant Digital Generation Teacher Efforts in Investing Digital Literacy in Early Childhood Education - Fitriyah, Qonitah Faizatul; Qaidatiningsih, Salmarani Putri; Nafisah, Shafa Oktavia (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2023)
Learning difficulties that many students experience are learning concentration, management of learning materials, storage of learning outcomes, and exploration of stored learning outcomes. With digital literacy, it can increase student independence in finding solutions to problems that arise during learning using various digital sources. However, this is a problem for teachers of the digital immigrant generation because of the large difference in the generation gap. The output targets are (1) research reports on teachers' efforts to instill digital literacy for early childhood, (2) research articles published in the journal